International qualifications - (:unkn) unknown (Publications Office of the European Union, 2012)
"An increasing number of qualifications - certificates and diplomas - are awarded at international level, outside the jurisdiction of national authorities. These 'non-State' qualifications have been developed and are awarded by a wide range of bodies, organisations and companies addressing various purposes. What unites this extreme variety of qualifications is that they are not restricted to a particular national system or territory. They are all qualifications whose exchange value is defined outside traditional national qualifications systems. This raises some key questions and challenges for policy-makers as well as users - be they individual citizens or employers. This report is a first effort to increase transparency in this field, notably by pointing to existing sources and clarifying the concepts to be used for mapping and analysis." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 2.2.4.3 Zertifizierung; L 6.2 Qualitätsmanagement/Qualitätssicherung; Interkulturelle Kompetenz; Begriff; Zertifizierung; Qualitätssicherung; Wirtschaftszweig